Foreign Investment, Regulatory Arbitrage, and the Risk of U.S. Banking Organizations - Frame, W. Scott; Mihov, Atanas; Sanz, Leandro (Journal of Financial and Quantitative Analysis, 2020)
This study investigates the implications of cross-country differences in banking regulation and supervision for the international subsidiary locations and risk of U.S. bank holding companies (BHCs). We find that BHCs are more likely to operate subsidiaries in countries with weaker regulation and supervision and that such location decisions are associated with elevated BHC risk and higher contribution to systemic risk. The quality of BHCs’ internal controls and risk management plays an important role in these location choices and risk outcomes. Overall, our study suggests that U.S. banking organizations engage in cross-country regulatory arbitrage, with potentially adverse consequences.